Bridging trauma and eating disorders: the role of loneliness - Meneguzzo, Paolo; Marzotto, Anna; Mezzani, Barbara; Conti, Fabio; Maggi, Luca; Todisco, Patrizia (Frontiers in Psychiatry, 2024)
IntroductionEating disorders (EDs) are complex and often linked to traumatic childhood experiences. While childhood trauma is known to increase the risk of EDs, the role of loneliness remains underexplored. This study investigates whether loneliness mediates the relationship between childhood trauma and ED symptoms.MethodsA total of 230 individuals with EDs completed the Childhood Trauma Questionnaire, the UCLA Loneliness Scale, and the Eating Disorders Examination Questionnaire. Mediation analysis was conducted to assess if loneliness mediates the relationship between childhood trauma and ED severity.ResultsChildhood trauma significantly predicted higher levels of loneliness (p < 0.001), which was associated with more severe ED symptoms (p = 0.001), with age and BMI as covariates. Mediation analysis showed loneliness partially mediated the relationship between childhood trauma and ED severity (indirect effect b = 0.003, 95%CI [0.001, 0.006]).ConclusionLoneliness partially mediates childhood trauma and ED symptoms, highlighting the need to address loneliness in treatment to mitigate the impact of childhood trauma on ED severity. These findings suggest the possible role of social connection-focused interventions in ED care and contribute to understanding the mechanisms underlying the development of EDs. Future research should explore additional mediators and moderators to provide a more comprehensive perspective.